Sistem Pakar Diagnosa Autisme Pada Anak Berbasis Android - Nurhakim, Nurhakim; Handayanna, Frisma; Rinawati, Rinawati (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2017)
Autism is a developmental disorder in children that causes child is difficult do communicte and interact socially. An expert system identification and treatment of autistic children based on android has not been widely applied, ussually only done manually based on the identification of a Psychologist assessment. Identification expert system is expected to assist in the identification of children with autism are much faster and accurate approach using data from Psychologists and special needs teachers. Knowledge in the expert system is represented in the form of rules and methods of reasoning and used method of trace forward chaining. Output on a system such as whether Three si The possibility of autism in child based on facts bor symptoms given to the system. The test results shaw that the system of identification Ana treatment of autistic children to help in the identification of children with autism and provide general description of the autistic child. In addition, there is also general information on children with autism and theirs methods of theraphy for children with autism in accordance with the conditions of the child.